2023
DOI: 10.1038/s41598-022-26091-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of fissure angle on energy evolution and failure characteristics of fractured rock under uniaxial cyclic loading

Abstract: To study the influence of fissure angle on the rock damage process and energy evolution characteristics, uniaxial cyclic loading and unloading tests were conducted on fractured rock specimens with different prefabricated fissure angles. The stress–strain curves, mechanical properties, and failure characteristics were analyzed. Subsequently, the energy evolution characteristics and failure mechanisms were investigated. The results showed that the stress–strain curves of fractured specimens fluctuated in the pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 8 publications
(6 reference statements)
0
2
0
Order By: Relevance
“…Rodríguez P et al [25] carried out loading and unloading splitting experiments on marble disks containing microcracks and focused on studying the crack propagation and evolution rules under the loading and unloading paths through the AE signal. Zhao Y et al [26] conducted uniaxial cyclic loading and unloading tests on rock specimens with different prefabricated crack angles and studied the influence of crack angles on energy evolution characteristics. Liu X et al [27] used uniaxial compression and CT scanning to carry out constant-amplitude cyclic and step-by-step cyclic loading and unloading tests on siltstone, revealing the propagation and failure mechanism of pore cracks in the surrounding rock mass of underground engineering under cyclic loading.…”
Section: Introductionmentioning
confidence: 99%
“…Rodríguez P et al [25] carried out loading and unloading splitting experiments on marble disks containing microcracks and focused on studying the crack propagation and evolution rules under the loading and unloading paths through the AE signal. Zhao Y et al [26] conducted uniaxial cyclic loading and unloading tests on rock specimens with different prefabricated crack angles and studied the influence of crack angles on energy evolution characteristics. Liu X et al [27] used uniaxial compression and CT scanning to carry out constant-amplitude cyclic and step-by-step cyclic loading and unloading tests on siltstone, revealing the propagation and failure mechanism of pore cracks in the surrounding rock mass of underground engineering under cyclic loading.…”
Section: Introductionmentioning
confidence: 99%
“…Characteristic strain rates were applied to evaluate the extent of fragmentation and these were compared to existing theoretical tensile fragmentation models. Zhao et al [20] studied the mechanical properties, damage behavior, energy dissipation characteristics, and damage mechanisms of fissured rock specimens with different prefabricated fissure angles. You et al [21] carried out triaxial dynamic tests on sandstone containing prefabricated cracks at different strain rates and concluded that the dynamic strength and energy dissipation density of sandstones increased with increasing strain rate.…”
Section: Introductionmentioning
confidence: 99%